Studi Kasus Pengaruh Efisiensi Supply Chain Terhadap Kinerja Pengelolaan Uang Tunai (Studi pada Divisi Sentra Layanan Perbankan Elektronik PT Bank Central Asia Tbk) - Anna Susilowati (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
Cash at PT Bank Central Asia no longer faced logistics issues but has turned into a matter of optimizing the cash management costs of the cash balance managed. The managed balance should consider the needs of customers in branches and ATMs. Therefore, researchers feel the need to establish the amount of cash needed to be available in the branch and to make an estimate of the amount of money to be prepared Not idle. The money that is idle can be a conference for other purposes that generate income from the interest rate. The target in this study is to achieve a target of cash management costs amounting to 0.2% of the cash balance managed. Analysis process to find the root of the problem has not achieved the target cost of management of cash is by using PDCA method (Plan, Do, Check, Action), Fishbone diagram and Pareto diagram. The result of the calculation of the ideal balance and the forecasting of the ATM replenishing the performance, which is very significant cost efficiency so that the target set can be achieved.